The vocal behavior of Ukrainians and Belarusians: peculiarities of communicative silence (on the basis of phraseology units) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
This paper is an attempt to consider the phenomenon of communicative silence as a specific component of non-verbal behavior in general. Multidimensional and multifunctional nature of silence gives scientist the reason to investigate this phenomenon in terms of linguistics, paralinguistics, psychology, cultural studies etc. It is stated that the semantic meaning of silence is revealed in specific situations, which represent the communicative competence of a person in a society. The general models of vocal behavior depend on the national and cultural traditions and in the same time they are closely related to the stereotypes presented in a certain language group. The laws of communication, non-verbal components of interpersonal interaction, paralinguistic units, which are communicatively significant and have a certain emotional color, have their reflection in the phraseology items of the Ukrainian and Belarusian languages. The idiomatic phrases representing the silence strategy contain the achievements of the socio-cultural experience of Ukrainians and Belarusians, as well as the process of changing the speakers’ communicative roles. This paper focuses on the semantics of the analyzed set expressions connected with the phenomenon of communicative silence. Their meaning demonstrates the position of the speaker in a communicative act, points to his/her psychological peculiarities, the national character. It should be noted that such silence strategy to some extent indicates the communicative inconsistency that arises as a result of non-fulfillment of the expected step-reaction. Also attention is paid to the phraseology units’ formation in the process of breaking linguistic interaction, in the aspect of anatomical and physiological possibilities of the person’s speech apparatus. Such intellectual actions involve the transfer of the knowledge relevant part about “the silence of the speaker” to the object of naming, which relates to various characteristics of human life: closing of the mouth, manipulation with the tongue, physical violence for silence. This research analyzes associative connections of the set expressions with the phenomena of the ending of life (a grave, a coffin), as a sign of absolute silence. A comparative analysis of Ukrainian and Belarusian silence idiomatic expressions represents the parallelism of their semantics and forms, which is shown by somatisms: a tongue, a mouth, a throat, lips and teeth. It is manifested that the movement of these organs and actions with them create a metaphorical basis for revealing human vocal behavior, especially the creation of a silence effect.
Keywords: phonetic phraseology unit; communicative silence; silence effect; metaphorization; non-verbal communication; somatism